2015
DOI: 10.1007/s00223-015-0093-3
|View full text |Cite
|
Sign up to set email alerts
|

Higher Level of Dickkopf-1 is Associated with Low Bone Mineral Density and Higher Prevalence of Vertebral Fractures in Patients with Ankylosing Spondylitis

Abstract: Patients with ankylosing spondylitis (AS) have an increased risk of bone loss and vertebral fractures. In this study, we explored the hypothesis that the excess bone loss and vertebral fractures might be related with the activity of the Wingless signaling pathway, and in particular with the serum levels of its circulating inhibitors, Sclerostin and Dickkopf-1 (DKK1). We recruited 71 patients diagnosed with AS. Lateral radiographs of the total spine were analyzed to detect the presence of vertebral fractures, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 43 publications
4
24
1
Order By: Relevance
“…Worsening osteoarthritis in low motion joints is often characterized by minimal evidence of synovitis, subchondral bone lysis, and a progression towards ankylosis (1). Previous studies have documented a direct correlation between bone erosion, osteopenia, and the overexpression of Dkk-1 (6,10,16). We anticipated that a similar relationship might exist in the horse, however no significant association was established when comparing subchondral bone lysis scores and Dkk-1 values.…”
Section: Patient S:p Ratio Under All Comparative Circumstancesmentioning
confidence: 84%
See 1 more Smart Citation
“…Worsening osteoarthritis in low motion joints is often characterized by minimal evidence of synovitis, subchondral bone lysis, and a progression towards ankylosis (1). Previous studies have documented a direct correlation between bone erosion, osteopenia, and the overexpression of Dkk-1 (6,10,16). We anticipated that a similar relationship might exist in the horse, however no significant association was established when comparing subchondral bone lysis scores and Dkk-1 values.…”
Section: Patient S:p Ratio Under All Comparative Circumstancesmentioning
confidence: 84%
“…In the horse, preliminary work has been done to characterize the Wnt-signalling molecules involved in the regulatory pathways of equine chondrocytes during development (15). More recently, Dkk-1 was found to be overexpressed in the early stages of equine osteochondrosis (16). The antagonism of the Wnt signalling pathway produced by Dkk-1 has been shown to be beneficial in rats with knee osteoarthritis by reducing cartilage fibrillation, subchondral bone damage, and serum degradation biomarkers (17).…”
Section: Introductionmentioning
confidence: 99%
“…Young patients with AS have low levels of active vitamin D3 and sclerostin (secreted from bone tissues and inhibits Wnt, a signaling factor necessary for bone formation by osteoblasts) and high dickkopf-1 levels [23][24][25][26][27] . Senolt et al reported that the critical bone formation factor, DKK-1, is low in the serum of patients with DISH.…”
Section: Discussionmentioning
confidence: 99%
“…In more detail, preclinical studies have shown that the overexpression of DKK1 causes osteopenia in mice, while reduced DKK1 expression is associated with high bone mass [43,44]. Furthermore, altered serum levels of DKK1, reported in patients with inflammatory rheumatic diseases, including RA and ankylosing spondylitis, suggest the involvement of DKK1 in bone loss in inflammatory arthropathies [45][46][47][48][49].…”
Section: Interactions Between the Immune System And The Skeletonmentioning
confidence: 99%